The Kolmogorov reverse equation and high energy multiplicity relations - Dewanto, A. (2014)
Proceedings of the Conference in Honour of Murray Gell-Mann's 80th Birthday: Quantum Mechanics, Elementary Particles, Quantum Cosmology and Complexity